Heart rate and blood pressure dependence of aortic distensibility in rats: comparison of measured and calculated pulse wave velocity. Issue 1 (January 2021) - Spronck, Bart; Tan, Isabella; Reesink, Koen D.; Georgevsky, Dana; Delhaas, Tammo; Avolio, Alberto P.; Butlin, Mark
Abstract : Objectives: When assessing arterial stiffness, heart rate (HR) and blood pressure (BP) are potential confounders. It appears that the HR/BP dependences of pulse wave velocity (PWV) and distensibility are different, even though both assess arterial stiffness. This study aims to compare aortic PWV as measured using pulse transit time (PWVTT ) and as calculated from distensibility (PWVdist ) at the same measurement site and propose a solution to the disparity in dependences of PWVTT and PWVdist . Methods: Adult anaesthetized rats ( n = 24) were randomly paced at HRs 300–500 bpm, at 50 bpm steps. At each step, aortic PWVTT (two pressure-tip catheters) and PWVdist (pressure-tip catheter and ultrasound wall-tracking; abdominal aorta) were measured simultaneously while BP was varied pharmacologically. Results: HR dependence of PWVdist paradoxically decreased at higher levels of BP. In addition, BP dependence of PWVdist was much larger than that of PWVTT . These discrepancies are explained in that standard PWVdist uses an approximate derivative of pressure to diameter, which overestimates PWV with increasing pulse pressure (PP). In vivo, PP decreases as HR increases, potentially causing a PWVdist decrease with HR. Estimating the full pressure-diameter curve for each HR corrected for this effect by enabling calculation of the true derivative at diastolic BP. This correction yielded a PWVdist that shows HR and BP dependences similar to those of PWVTT . As expected, BP dependence of all PWV metrics was much larger than HR dependence. Conclusion: Measured and calculated PWV have different dependences on HR and BP. These differences are, at least in part, because of approximations made in using systolic and diastolic values to calculate distensibility. Abstract : Supplemental Digital Content is available in the text